THE NEEDS ANALYSIS OF TRAINING FOR ELEMENTARY SCHOOL TEACHERS (PRIOR ANALYSIS TO THE RESEARCH OF PROFESSIONAL AND PEDAGOGICAL COMPETENCIES DEVELOPMENT IN CIVICS EDUCATION) - Mawardi, Mawardi (Dewantara, 2013)
Purpose?Research on teacher training needs analysis in order to study the development of pedagogical and professional elementary school teachers competencies in Civic education aims to describe the level of pedagogical and professional? elementary school teachers competencies gap and to describe the elementary teacher training needs in order to develop pedagogical and professional deficit. Method?This study is a descriptive research. The study sites spread across the elementary school teachers in 8 subdistricts which are Suruh, Bancak, Bringin, Pabelan, Tengaran, Kaliwungu, Getasan and Ambarawa. The sample consists of 72 teachers, taken by purposive clusters sampling. Data collection technique is using self-evaluation in the form of questionnaire that has been tested for the validity and reliability. Analysis showed that the corrected item-total correlation is 0,794 for the highest and 0,221 for the lowest. Reliability test results showed that the alpha reliability coefficient is 0.945. Moreover, the techniques of data analysis are using descriptive statistical analysis and gap analysis. Findings ?The result of the analysis shows that there are1) the gap of teachers? pedagogic competency is 23.07 %, 2) the gap of teachers professional competency is 30 % , dan 3) the gap of pedagogic and professional competencies includes;(a) developing the curriculum which is related to Civics Education, (b) conducting assesment and evaluation of the process and result of learning process, (c) using the result of assesment and evaluation for the sake of teaching and learning, (d) Doing refective action (Class Action Research) to enhance teaching and learning process, (e) mastering the concept and principle of protection and development of Human Rights and also fair and proper law enforcement, (f) developing the material of civics education creatively, (g) developing sustainable profesionalism through reflective action, (h) using information technology and communication for self developing action. Significance?This research discusses about the gap of elementary school teachers? competencies, spesifically civics education. Gap occurs when there is discrepancy between ideal competencies and empirical competencies of teachers? performance. The results of this research are useful for designing training in teachers? competence. Keywords: The need for training, pedagogic and professional competence, civics education